2018
DOI: 10.1071/cp18178
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis for seed yield, forage yield and traits related to drought tolerance in orchardgrass (Dactylis glomerata)

Abstract: Polycross designs bridge the two usual mapping approaches (bi-parental mapping and association analysis) and increase mapping power by incorporating greater genetic diversity. In this study, we used diverse genotypes selected from polycrossed progenies to identify marker loci associated with a set of seed- and forage-related traits as well as drought tolerance in orchardgrass (Dactylis glomerata L.). Associations were estimated between phenotypic traits and 923 DNA markers (including 446 inter-simple sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Based on the results of GLM and MLM models, some markers had simultaneously signi cant associations with more than one trait. These markers may be effectively used for the improvement of several traits, concurrently [33,34]. Multi-association among different traits could be attributed to the coexpression mediated by expression of quantitative trait loci or e-QTLs [48].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of GLM and MLM models, some markers had simultaneously signi cant associations with more than one trait. These markers may be effectively used for the improvement of several traits, concurrently [33,34]. Multi-association among different traits could be attributed to the coexpression mediated by expression of quantitative trait loci or e-QTLs [48].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of GLM and MLM models, some markers had simultaneously significant associations with more than one trait. These markers may be effectively used for the improvement of several traits, concurrently [33,34]. Multi-association among different traits could be ascribed to coexpression mediated by expression of quantitative trait loci or e-QTLs [49].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, some markers had simultaneously significant associations with more than one trait and may be effectively used for the improvement of several traits, concurrently (Sun et al ., 2015; Abtahi et al ., 2018b). Association between multiple traits could be attributed to the co-expression mediated by expression of quantitative trait loci or e-QTLs (House et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, association analysis in forage grasses is applied extensively for dissecting the genetic bases of different quantitative traits in several species such as perennial ryegrass ( Lolium perenne ) (Auzanneau et al ., 2011; Yu et al ., 2011; Tang et al ., 2013; Yu et al ., 2013), tall fescue ( Festuca arundinacea ) (Lou et al ., 2015; Sun et al ., 2015), and orchardgrass ( Dactylis glomerata L.) (Yan et al ., 2016; Zhao et al ., 2017; Abtahi et al ., 2018b). These studies have demonstrated that GWAS is an efficient technique for identifying genomic regions linked to the quantitative traits.…”
Section: Introductionmentioning
confidence: 99%